COVID-19 in hospitalized lung and non-lung solid organ transplant recipients: A comparative analysis from a multicenter study - VELİOĞLU, ARZU (WILEY, 2021)
Lung transplant recipients (LTR) with coronavirus disease 2019 (COVID-19) may have higher mortality than non-lung solid organ transplant recipients (SOTR), but direct comparisons are limited. Risk factors for mortality specifically in LTR have not been explored. We performed a multicenter cohort study of adult SOTR with COVID-19 to compare mortality by 28 days between hospitalized LTR and non-lung SOTR. Multivariable logistic regression models were used to assess comorbidity-adjusted mortality among LTR vs. non-lung SOTR and to determine risk factors for death in LTR. Of 1,616 SOTR with COVID-19, 1,081 (66%) were hospitalized including 120/159 (75%) LTR and 961/1457 (66%) non-lung SOTR (p = .02). Mortality was higher among LTR compared to non-lung SOTR (24% vs. 16%, respectively, p = .032), and lung transplant was independently associated with death after adjusting for age and comorbidities (aOR 1.7, 95% CI 1.0-2.6, p = .04). Among LTR, chronic lung allograft dysfunction (aOR 3.3, 95% CI 1.0-11.3, p = .05) was the only independent risk factor for mortality and age >65 years, heart failure and obesity were not independently associated with death. Among SOTR hospitalized for COVID-19, LTR had higher mortality than non-lung SOTR. In LTR, chronic allograft dysfunction was independently associated with mortality.
Keywords: clinical research; practice; infection and infectious agents; viral; infectious disease; lung (allograft) function; dysfunction; lung disease; infectious; lung transplantation; pulmonology; organ transplantation in general